2009
DOI: 10.1186/1471-2202-10-144
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced motor improvement after complete spinal cord transection and its relation to expression of brain-derived neurotrophic factor and presynaptic markers

Abstract: BackgroundIt has been postulated that exercise-induced activation of brain-derived neurotrophic factor (BDNF) may account for improvement of stepping ability in animals after complete spinal cord transection. As we have shown previously, treadmill locomotor exercise leads to up-regulation of BDNF protein and mRNA in the entire neuronal network of intact spinal cord. The questions arise: (i) how the treadmill locomotor training, supplemented with tail stimulation, affects the expression of molecular correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 72 publications
(98 reference statements)
9
59
2
Order By: Relevance
“…Our study was not designed to identify whether sprouting or spared axons show increased synaptic transmission, but we did examine changes in synaptophysin, a synaptic vesicle protein that is present in presynaptic axons. Previous studies demonstrated that synaptophysin immunoreactivity is reduced in the spinal cord caudal to the lesion site after spinal cord hemisection or transection (Nacimiento et al, 1995;Macias et al, 2009;Ló pez-Dolado et al, 2013), which is similar to our data. The decreased global synaptophysin expression caudal to the lesion site in our vehicle-treated group was not present in DHA-treated animals.…”
Section: Discussionsupporting
confidence: 83%
“…Our study was not designed to identify whether sprouting or spared axons show increased synaptic transmission, but we did examine changes in synaptophysin, a synaptic vesicle protein that is present in presynaptic axons. Previous studies demonstrated that synaptophysin immunoreactivity is reduced in the spinal cord caudal to the lesion site after spinal cord hemisection or transection (Nacimiento et al, 1995;Macias et al, 2009;Ló pez-Dolado et al, 2013), which is similar to our data. The decreased global synaptophysin expression caudal to the lesion site in our vehicle-treated group was not present in DHA-treated animals.…”
Section: Discussionsupporting
confidence: 83%
“…Synaptophysin labeling was found primarily on the perimeter of motor neurons. Simple PCI 6 software (Compix, Inc. PA) was used to analyze synaptophysin labeling based on a technique developed by Macias and associates for analyzing synaptophysin around motor neurons (Macias et al, 2009). Using the elliptical object drawing tool, an outline was generated that extended just beyond the perimeter of HSP27-labeled motor neurons.…”
Section: Microscopic Imaging and Analysesmentioning
confidence: 99%
“…Moreover, biochemical and anatomical changes in the spinal cord were not examined in our previous study; therefore, the extent to which the different amounts of WSTT impacted the spinal cord circuitry was not known. A recent study has shown that the amount of synaptic inputs to motor neurons was greater in spinally transected (ST) rats that received daily treadmill training for 4 weeks (16-24 min/training session) relative to untrained ST rats (Macias et al, 2009). In addition, the ratio of excitatory to inhibitory synapses was increased in trained relative to untrained ST rats (Ichiyama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that synaptic inputs onto motor neurons found in the locomotor-generating region of the spinal cord were increased by treadmill training in spinally transected rats [64][65]. There is also evidence that treadmill training restored a normal balance of excitatory to inhibitory synapses, thereby improving motor neuron activity [45].…”
Section: Possible Influence Of Fes+rtt On Spinal Circuitrymentioning
confidence: 97%